Forest Land Change Assessment of Karang Mumus Sub-Watershed Area - Sri Endayani; Andrew Stefano; Fathiah; Hamka; Andi Lisnawati: (Institut Pertanian Bogor (IPB University), 2023)
Karang Mumus watershed is an important area as a port and gateway to the inland of East Kalimantan, causing the trade sector and water transportation services in this city to be very developed. Traders and immigrants from various regions who came in, stopped by, performed business, and stayed have caused the riverbanks to develop into economic and trade centers. One of the issues in the Karang Mumus sub-watershed is the conversion of forest area to agricultural land. With the improper use of agrotechnology and soil conservation, agricultural operations result in erosion and reduced land yield. This study aims to evaluate the Karang Mumus sub-potential watersheds to support land capability by using the overlay method (geoprocessing) of a geographic information system (GIS) based on criteria for classifying land capabilities and a data analysis approach. The findings revealed that the Karang Mumus sub-land watersheds primarily are categorized as land capacity class III, with a moderate erosion limiting factor that covers 15,864 ha (50.45%). The remaining areas are categorized into land capability classes IV and VI, with class IV having a severe slope limiting factor and class VI having a severe slope limiting factor with a fairly strong soil sensitivity to erosion, covering 8,751.14 ha (27.83%) and 6,829.85 ha (21.72%), respectively. Class III land is recommended for agricultural cultivation, application of appropriate agro-technology, and soil and water conservation. This study recommends that class IV and VI lands area are used for community forests or plantation forests managed by government agencies involved in the forest area stabilization center (BPKH) Region IV Samarinda.